Tuber melanorufum and T. tomentellum, two new truffle species from China - Fu, Hao-Yu; Fan, Li (Phytotaxa, 2023)
Tuber melanorufum and T. tomentellum spp. nov. are described and illustrated in this paper based on the morphological and phylogenetic data. Tuber melanorufum is diagnosed by the red-brown to blackish ascomata covered with distinctly fine warts and the ellipsoid to long ellipsoid ascospores ornamented with very crowded spine-reticulations. Tuber tomentellum is characterized by the large ascospores and two types of hairs arising from the outer cells of the peridium. Phylogenetic analyses place T. melanorufum and T. tomentellum in the Rufum and Puberulum clades, respectively.